Climatic Correlates of Brucellosis Transmission in a Semi-Arid Region of Xinjiang, China, 2015–2025: A Maximum Entropy Modeling Study Within a One Health Framework - Yuerong Lv; Xiang Gao (Animals, 2026)
More than 80% of global brucellosis cases occur in semi-arid regions; however, the climatic factors associated with these outbreaks remain poorly understood. This study investigated environmental correlates of brucellosis in a semi-arid region of Xinjiang, China. A maximum entropy (MaxEnt) model incorporating 19 bioclimatic variables, wind speed, solar radiation, and ruminant livestock inventory was applied to 1132 surveillance-confirmed human brucellosis cases from January 2015 to December 2025. Precipitation in the driest month (31.8%), wind speed (24.3%), and temperature seasonality (13.7%) were the leading contributors to the predicted risk. The model identified high-risk zones in low-precipitation moderate-wind steppe environments and showed strong predictive performance (AUC = 0.960 ± 0.007). These findings indicate that water scarcity and thermal variability are key environmental constraints associated with brucellosis distribution in semi-arid ecosystems and may inform climate-resilient One Health-based prevention strategies in similar agro-ecological zones globally.